Pseudotyping of lentiviral vector with novel vesiculovirus envelope glycoproteins derived from Chandipura and Piry viruses - Hu, Shuang, author; Akkina, Ramesh, advisor; Quackenbush, Sandra, committee member; Aboellail, Tawfik, committee member; Ryan, Elizabeth, committee member (Colorado State University. Libraries, 2016)
Lentiviral vector system is widely used in gene therapy. Although the envelope glycoprotein of vesicular stomatitis virus (VSV-G) has been mostly used to pseudotype lentiviral vectors, its disadvantages such as low transduction levels in certain cell types and sensitivity to inactivation by human complement hinders the usage of VSV-G pseudotyped lentiviral vectors in some cells or its direct in vivo clinical application. Aiming at overcoming some of these drawbacks of VSV-G, we evaluated two novel vesiculovirus envelope glycoproteins from Chandipura virus and Piry virus (CNV-G and PRV-G), as alternatives to VSV-G. Our results showed that pseudotyped lentiviral vectors could be generated with both these envelopes with high titers and stabilities similar to VSV-G. While displaying a more selective tropism than VSV-G, both CNV-G and PRV-G pseudotypes were found to be efficient in transducing a variety of cell types that include neuronal, fibroblastic and epithelial cells from across different species in addition to a number of human T-lymphocyte cell lines in vitro. Additionally, both the novel pseudotypes were found to be more resistant to human sera inactivation than the VSV-G pseudotype, thus providing better candidates for systemic administration. These data, taken together, establish that both Chandipura and Piry viral glycoproteins are suitable alternative candidates for lentiviral vector pseudotyping with an additional advantage for potential in vivo use in various gene therapy-based applications.
Keywords: gene transduction with pseudotyped lentiviral vectors; Lentiviral vector pseudotyping; human serum resistant lentiviral vectors; Chandipura and Piry viral glycoproteins